The influence of long-chain Omega-3 fatty acids on eccentric exercise-induced delayed muscle soreness: Reported outcomes are compromised by study design issues - Anthony, R.; Macartney, M. J.; Peoples, G. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Delayed onset muscle soreness (DOMS) following eccentric exercise is associated with increased inflammation which can be debilitating. Incorporation of long-chain omega-3 polyunsaturated fatty acids (LC n-3 PUFA), eicosapentaenoic acid, and docosahexaenoic acid into membrane phospholipids provides anti-inflammatory, proresolving, and analgesic effects. This systematic review aims to examine both the quality of studies and the evidence for LC n-3 PUFA in the attenuation of DOMS and inflammation following eccentric exercise, both which of course are empirically linked. The Scopus, Embase, and Web of Science electronic databases were searched to identify studies that supplemented fish oil for a duration of =7 days, which included DOMS outcomes following an eccentric exercise protocol. Fifteen (n = 15) studies met inclusion criteria. Eccentric exercise protocols varied from single to multijoint activities. Risk of bias, assessed using either the Cochrane Collaboration tool or the Risk of Bias in Nonrandomized Studies of Interventions tool, was judged as "unclear" or "medium," respectively, for the majority of outcomes. Furthermore, a custom 5-point quality assessment scale demonstrated that only one (n = 1) study satisfied current recommendations for investigating LC n-3 PUFA. In combination, this highlights widespread inappropriate design protocols among studies investigating the role of LC n-3 PUFA in eccentric exercise. Notwithstanding these issues, LC n-3 PUFA supplementation appears to have favorable effects on eccentric exercise-induced DOMS and inflammatory markers. However, the optimal LC n-3 PUFA supplemental dose, duration, and fatty acid composition will only become clear when study design issues are rectified and underpinned by appropriate hypotheses.